Soil-Plant-Ni-As: Four-Fold Interactions – Modest Blessing from Total Disguise - Sanchary, Ishrat Jahan; Begum, Monoara; Kabir, Kazi Md. Jahangir (European Journal of Applied Sciences, 2022)
As an essential plant nutrient, deficiency of nickel (Ni) can cause metabolic and enzymatic disorder in plants; however an excess amount of this element can also be proven deadly for a plant. To examine the critical level of Ni tolerance two plant species, Kalmi (Ipomoea aquatica) and Red Amaranthus (Amaranthus cruentus) were selected where Red Amaranthus (Amaranthus cruentus) was verified as a hyper accumulator of Ni. In this diverse experimental set up, arsenic (As) was applied with irrigation water and increased doses of Ni was observed to put antagonistic effect on availability as well as plant uptake of As. The results from such a complex and diverse four-fold interaction can be concluded as a little blessing of remediation of As toxicity from a disguise of Ni toxicity.